Efektivitas Pelayanan BPHTB Terhadap Kepuasan Wajib Pajak Pada Bapenda Kota Medan (Studi Kualitatif) - Silvi Dwi Ningrum; Desy Mahdalia; Henny Adriani Wirananda (STARLA: Jurnal Pengabdian Masyarakat, 2026)
This community service activity was conducted to directly observe the quality of Land and Building Acquisition Tax (BPHTB) services at the Medan City Regional Revenue Agency (Bapenda) and its impact on taxpayer satisfaction. BPHTB is a crucial source of Regional Original Revenue (PAD), so the quality of service provided to the public is crucial. Good service not only streamlines the administrative process but also builds public trust in the local government. This activity used a qualitative approach through observation, interviews, and documentation throughout the service process. The results showed that BPHTB services at the Medan City Bapenda were running quite well. This was evident in the clear service flow, friendly staff, and relatively easy-to-understand administrative processes. However, several obstacles remained, such as a lack of taxpayer understanding of BPHTB procedures and suboptimal socialization of digital-based services. Through this community service activity, students provided education and assistance to taxpayers to better understand the stages of BPHTB processing. This assistance resulted in a smoother service process and increased taxpayer satisfaction.